The effects of angiotensin converting enzyme inhibitors (ACEI) on human N-acetylseryl-aspartyl-lysyl-proline (AcSDKP) levels : a systematic review - Mnguni, Ayanda Trevor (Department of Medicine, 2016)
Background: Tuberculous pericardial effusion is a pro-fibrotic condition that is complicated by constrictive pericarditis in 4-8% of cases. N-acetyl-seryl-aspartyl-lysylproline (Ac-SDKP) is a ubiquitous tetrapeptide with antifibrotic properties that is low in tuberculous pericardial effusion, thus providing a potential mechanism for the heightened fibrotic state. Angiotensin converting enzyme inhibitors (ACEI), which increase Ac-SDKP levels with antifibrotic effects in animal models, are candidate drugs for preventing constrictive pericarditis if they can be shown to have similar effects on AcSDKP and fibrosis in human tissues. Objective: To systematically review the effects of ACEIs on Ac-SDKP levels in human tissues. Methods: We searched five electronic databases (1996-2014) and conference abstracts with no language restrictions. Two reviewers independently selected studies, extracted data and assessed methodological quality. The protocol was registered in PROSPERO.